Where love grows [large type] - Eicher, Jerry S. (Eicher, Jerry S. Fields of home, 2013)
In the conclusion to the Fields of Home trilogy, the young English girl, Teresa, finds love among the Amish and marries the man of her dreams, while her sponsor, Susan Hostetler, must choose between an old love and a new.